2005
DOI: 10.1038/sj.bjc.6602465
|View full text |Cite
|
Sign up to set email alerts
|

Familial aggregation of lung cancer in a high incidence area in China

Abstract: To investigate whether lung cancer clusters in families in a high incidence county of China, an analysis was conducted using data on domestic fuel history and tobacco use for family members of 740 deceased lung cancer probands and 740 controls (probands' spouses). Lung cancer prevalence was compared among first-degree relatives of probands and of controls, taking into account various factors using logistic regression and generalised estimating equations. First-degree relatives of probands, compared with those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 24 publications
1
12
0
1
Order By: Relevance
“…Among 31 independent case-control studies published since the first report of familial aggregation of lung cancer in 1963, 29 30 studies showed consistently positive associations, with ORs ranging from 1.2 to 5.3. 3,4,14,15,17,18,22,23,[26][27][28][29][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] Only one small study with 185 subjects showed a reverse association. 52 Similarly, all 6 cohort studies showed significant positive associations.…”
Section: Discussionmentioning
confidence: 99%
“…Among 31 independent case-control studies published since the first report of familial aggregation of lung cancer in 1963, 29 30 studies showed consistently positive associations, with ORs ranging from 1.2 to 5.3. 3,4,14,15,17,18,22,23,[26][27][28][29][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] Only one small study with 185 subjects showed a reverse association. 52 Similarly, all 6 cohort studies showed significant positive associations.…”
Section: Discussionmentioning
confidence: 99%
“…2 Once tumor cells have spread, the long-term prognosis is poor because no curative treatments are available. All kinds of epigenetic events, such as promoter methylation, are suspected of participating in the pathogenesis and progression of lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, there seems to be a genetic susceptibility to developing the disease in both smokers and non smokers as recent familiar aggregation studies have shown. [23][24][25] Supporting this evidence are several molecular studies that have found polymorphism in several detoxifying or DNA repairing enzymes associated with lung cancer risk. 26,27 Also, particularly in females, biomass use has been positively associated with lung cancer risk in several epidemiologic studies.…”
Section: Discussionmentioning
confidence: 74%